If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1100000 = (-40000) * x + 1512000 Reorder the terms: 1100000 = 1512000 + -40000x Solving 1100000 = 1512000 + -40000x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40000x' to each side of the equation. 1100000 + 40000x = 1512000 + -40000x + 40000x Combine like terms: -40000x + 40000x = 0 1100000 + 40000x = 1512000 + 0 1100000 + 40000x = 1512000 Add '-1100000' to each side of the equation. 1100000 + -1100000 + 40000x = 1512000 + -1100000 Combine like terms: 1100000 + -1100000 = 0 0 + 40000x = 1512000 + -1100000 40000x = 1512000 + -1100000 Combine like terms: 1512000 + -1100000 = 412000 40000x = 412000 Divide each side by '40000'. x = 10.3 Simplifying x = 10.3
| 254=x-122 | | 8x^2-46x+63=0 | | 3y^2-4y-8=0 | | x-122=254 | | x(x-1)(x-2)(x-3)=180(x-1)(x-2) | | 6yx-5x^2=4 | | 6xy-5y^2=4 | | 5x^4+12x^2=0 | | =3x^4-4x^3-12x^2+15 | | 2(5x-4)=x+9 | | 4x^2-16x=65 | | 8x^3-8x^2=3 | | 60+42.95m=25+49.95m | | (x-7)=64 | | 4f+6f= | | 8x^3-8x^2-3=0 | | 147=3*x*x | | -2y-4=4(4y-1) | | 15=5y-4x | | 36=2*6*c | | (4x+3)2=5 | | 9=2(7-b) | | f(x)=3x^4-4x^3-12x^2+15 | | -z^2-iz-1=0 | | y=0.5871e^2l | | 14=2(4+b) | | 8(2+x)=5(3x+x)-11 | | 13=m*5-7 | | 6y+9=31 | | 3=3x^2-7x | | 5x+2y=11-xy | | 7a=2a |